EFFECT OF SUGARCANE BY-PRODUCT BASED COMPLETE RATIONS ON NUTRIENT UTLIZATION AND MILK PRODUCTION IN MURRAH BUFFALOES* (Indian Journal of Animal Production and Management, 2014)
Seven rations (six complete rations were formulated by using sugarcane by products and other crop residues and balanced concentrate mixture in the mash form and one conventional ration comprised with hybrid Napier and concentrate mixture) were prepared and fed to 28 Murrah buffaloes for a period of 180 days using Randomized Block Design to study the effect of processing of complete diet on nutrient utilization and milk production. The DMI (kg/100kgbody wt) was significantly (P
Keywords: Sugarcane by-products; complete ration; milk production; Murrah buffaloes